Biaxially oriented polyester film roll and its manufacturing method

JP7632551B2Active Publication Date: 2025-02-19TOYOBO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023163659
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-03
Filing Date
2023-09-26
Publication Date
2025-02-19
Estimated Expiration
2041-08-06

AI Technical Summary

Benefits of technology

【0019】 本発明により、優れた透明性、機械特性を有するとともに、フィルムの製造工程中の滑り性や巻取り性にも優れており、ペットボトルを含む、市場や社会からリサイクルされたポリエステル樹脂)を用いることにより、環境配慮されたポリエステルフィルムロールであると共に、巻長の長い長尺のフィルムロールであっても長手方向の物性のバラつきの少ない二軸配向ポリエステルフィルム及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632551000004
    Figure 0007632551000004
  • Figure 0007632551000005
    Figure 0007632551000005
  • Figure 0007632551000006
    Figure 0007632551000006
Patent Text Reader

Abstract

To provide a biaxially oriented polyester film roll that has excellent transparency and mechanical properties, as well as excellent slipperiness and winding properties during a film manufacturing process, wherein the biaxially oriented polyester film roll is environmentally friendly and has little variation in physical properties in a longitudinal direction even if the biaxially oriented polyester film roll is a long film roll with a long winding length by using a polyester resin recycled from market and society, including PET bottles, and a manufacturing method of the same.SOLUTION: A biaxially oriented polyester film roll is made by winding a biaxially oriented polyester film consisting of a polyester resin composition containing recycled polyester resin and particles from market and society, including PET bottles, and the biaxially oriented polyester film roll has haze, a friction coefficient, an arithmetic mean height Sa, a maximum protrusion height Sp, and variation thereof within predetermined ranges.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biaxially oriented polyester film roll and a manufacturing method thereof, and more particularly to a biaxially oriented polyester film roll which has excellent transparency and mechanical properties, as well as excellent slip properties and winding properties during the film manufacturing process, and which is an environmentally friendly polyester film roll made by using polyester resin recycled from the market or society, including PET bottles (hereinafter, may be referred to as "polyester resin made from recycled PET bottles"), and which has little variation in physical properties in the longitudinal direction even in a long film roll with a long wound length, and a manufacturing method thereof. [Background technology]

[0002] Polyester resins such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), which are thermoplastic resins with excellent heat resistance and mechanical properties, are used in a wide variety of fields, including plastic films, electronics, energy, packaging materials, automobiles, etc. Among plastic films, biaxially oriented polyester films are widely used in industrial and packaging fields because they offer an excellent balance between mechanical strength, heat resistance, dimensional stability, chemical resistance, optical properties, and cost.

[0003] In the field of industrial films, due to its excellent transparency, it can be used as a functional film for flat panel displays (FPDs) such as liquid crystal displays and plasma displays. PET films with hydrolysis resistance are also used as backsheet films for solar cells, and are used for various purposes as functional films and base films.

[0004] In the field of packaging films, they are used for food packaging and as gas barrier films. In particular, films with excellent gas barrier properties are used as packaging materials that require airtightness for foods, medicines, electronic components, etc., or as gas blocking materials, and the demand for them has been increasing in recent years.

[0005] For example, Patent Document 1 describes a biaxially oriented polyethylene terephthalate film made from recycled PET bottle materials, which has a melt resistivity of 1.0×10 at a temperature of 285° C. 8 A biaxially oriented polyester film is disclosed, characterized in that the film has a viscosity of within Ω·cm and the sodium and potassium contents are greater than 0 ppm and not greater than 150 ppm. This technology makes it possible to obtain a biaxially oriented polyester film that has excellent thermal stability, little residual components of the cleaning solution used in producing recycled PET bottle raw materials, little foreign matter, and stable resistivity when melted, without compromising the productivity and quality of the film.

[0006] However, in order to improve productivity, a method for manufacturing a high-quality polyester resin sheet without surface defects such as pinner bubbles by increasing the rotation speed of a cooling drum and adjusting the position, current value, and voltage value of a wire-shaped electrode is mentioned, but no mention is made of the slipperiness during the film manufacturing process or the winding property of a film roll. In order to improve slipperiness, silica particles with an average particle diameter of 2.5 μm are used, and the amount of silica in the film is added to 150 ppm to 640 ppm, but the arithmetic mean height Sa and maximum protrusion height Sp tend to be low, and when the biaxially oriented polyester film is wound up, the air wound into the roll does not escape uniformly, which causes problems such as wrinkles and bubble-like acne, and the productivity and quality of the film are not sufficiently considered.

[0007] As described above, the polyester film has excellent transparency and mechanical properties, and is also excellent in slipperiness and winding properties during the film manufacturing process. As a means for obtaining an environmentally friendly polyester film by using polyester resin recycled from the market or society, including PET bottles, it is expected that the polyester resin composition containing particles and polyester resin recycled from the market or society, including PET bottles, can be obtained by biaxial stretching. It is common to mix resin chips with normal specific gravity and resin chips with high specific gravity containing particles to form a film. However, since the specific gravity difference between the resin chips containing particles and the normal resin chips is large, the raw material ratio is likely to vary during the mixing and extrusion process due to segregation of these raw material resin chips, and physical property differences occur in the longitudinal direction of the film. As a result, there are cases where a product with uniform physical properties cannot be obtained in the longitudinal direction of a long product roll. Since polyester resin recycled from PET bottles contains an isophthalic acid component and contains a large amount of amorphous components, the stretching stress during stretching is lower than that of conventional polyester resins derived from fossil fuels, and lubricants such as inorganic particles are more likely to sink. As a result, the surface roughness of the biaxially oriented polyester film tends to be low, and there are cases in which sufficient slip properties and film roll winding properties cannot be obtained. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 6036099 Summary of the Invention [Problem to be solved by the invention]

[0009] The object of the present invention is to provide a biaxially oriented polyester film roll and a manufacturing method thereof that overcomes the problems of the conventional technology, has excellent transparency and mechanical properties, as well as excellent slipperiness and winding properties during the film manufacturing process, and is environmentally friendly by using polyester resin recycled from the market and society, including PET bottles, and more preferably has a biaxially oriented polyester film roll with less foreign matter and little variation in physical properties in the longitudinal direction even in a long film roll with a long wound length, and a manufacturing method thereof. [Means for solving the problem]

[0010] As a result of intensive research by the present inventors, in a biaxially oriented polyester film obtained by biaxially stretching a polyester resin composition in which a polyester resin containing particles is blended with a polyester resin recycled from the market or society, including PET bottles, when mixing the raw material resin chips, the polyester resin chips recycled from the market or society, including PET bottles, are supplied from above to the hopper, and the polyester resin chips containing particles are supplied through a pipe (hereinafter sometimes referred to as an inner pipe) having an outlet in the hopper and directly above the extruder, and the two chips are mixed and melt extruded, whereby a uniform film with little variation in physical properties in the longitudinal direction of the film can be obtained. Furthermore, the present inventors have found that even if alkaline cleaning is performed to remove foreign matter when producing recycled raw materials from the market or society, including PET bottles used in the present invention, not only is there little remaining of the cleaning solution components used, and there is little foreign matter, but also that the slipperiness and winding property during the film manufacturing process can be improved by setting the maximum protrusion height on the film surface to a specific height or less, leading to the completion of the present invention.

[0011] That is, the present invention comprises the following: 1. A biaxially oriented polyester film roll obtained by winding up a biaxially oriented polyester film made of a polyester resin composition containing a polyester resin and particles made from recycled PET bottles, said biaxially oriented polyester film roll satisfying all of the following requirements (1) to (4): (1) The maximum projection height Sp of at least one of the film surfaces is 3.0 μm or less. (2) The haze at a film thickness of 12 μm is 10% or less. (3) The air escape time between the front and back surfaces of the film is 14 seconds or less. (4) When samples are taken every 1,000 m in the longitudinal direction of the film from the surface of the film roll to the core, the variation in both the arithmetic mean height Sa and the maximum projection height Sp is 40% or less. (The variation is expressed by the following formula [1], where the maximum value is Xmax, the minimum value is Xmin, and the average value is Xave. Variance (%) = 100 x (Xmax - Xmin) / Xave [1]

[0012] 2. The biaxially oriented polyester film according to 1., wherein the polyester resin made from recycled PET bottles is a mechanically recycled polyester resin and / or a chemically recycled polyester resin.

[0013] 3. The biaxially oriented polyester film roll described in 1. or 2., characterized in that the content of isophthalic acid components relative to 100 mol% of all dicarboxylic acid components in the polyester resin composition constituting the biaxially oriented polyester film is 0.01 mol% or more and 2.0 mol% or less.

[0014] 4. 100m of film 2 4. The biaxially oriented polyester film roll according to any one of 1. to 3., wherein the number of defects of 1 mm or more per roll is less than 20.

[0015] 5. The biaxially oriented polyester film roll according to any one of 1. to 4., wherein the dynamic friction coefficient between one surface and the opposite surface of the biaxially oriented polyester film is 0.20 or more and 0.60 or less.

[0016] 6. The biaxially oriented polyester film roll according to any one of 1. to 5., wherein the content of inorganic particles in all layers of the biaxially oriented polyester film is 100 ppm or more and 1000 ppm or less.

[0017] 7. The biaxially oriented polyester film roll according to any one of 1. to 6., wherein the polyester resin recycled from PET bottles has been subjected to alkali washing at least once.

[0018] 8. A method for producing a biaxially oriented polyester film roll according to any one of 1. to 7., comprising a polyester raw material resin melt extrusion step, a biaxial stretching step, and a step of winding up the biaxially stretched film into a roll, characterized in that in the polyester raw material resin melt extrusion step, raw material resin chips of the polyester resin recycled from the PET bottles are supplied from above to a hopper, and raw material resin chips of a polyester resin composition containing the particles are supplied through a pipe in the hopper having an outlet immediately above the extruder, to mix the two chips and melt extrude them. Effect of the Invention

[0019] The present invention can provide a biaxially oriented polyester film and its manufacturing method, which has excellent transparency and mechanical properties, as well as excellent slip properties and winding properties during the film manufacturing process, and is an environmentally friendly polyester film roll made by using polyester resin recycled from the market and society, including PET bottles, and which has little variation in physical properties in the longitudinal direction even in a long film roll with a long wound length.

[0020] In particular, in recent years, in order to improve the production efficiency of biaxially oriented polyester films, efforts have been made to increase the width and length of the biaxially oriented polyester film roll (hereinafter referred to as the master roll) that is first wound up after the stretching process. However, even with such large film rolls, the air that is entrained when the biaxially oriented polyester film is wound up does not escape evenly, resulting in a biaxially oriented polyester film that is easy to perform secondary processing and has fewer appearance defects such as wrinkles and air bubble-like pimples, as well as less blocking. The same is true for film rolls that are made by slitting the master roll into smaller pieces. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is a schematic diagram for explaining an example of a method for mixing resin chips to produce the biaxially oriented polyester film of the present invention. [Diagram 2] FIG. 2 is a partially enlarged view of FIG. [Diagram 3] FIG. 13 is an explanatory diagram of air release time measurement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will be described in detail below. [Polyester resin made from recycled PET bottles] As the polyester resin in the present invention made by recycling PET bottles, either a polyester resin obtained by a physical regeneration method in which used PET bottles collected from the market or society are sorted, crushed, and washed to thoroughly remove surface dirt and foreign matter, and then exposed to high temperatures to thoroughly wash away contaminants remaining inside the resin, and then the bottles are pelletized again (hereinafter, this may be referred to as a mechanically recycled polyester resin) or a polyester resin obtained by decomposing polyester resin contained in used packaging containers to the monomer level, removing contaminants, and polymerizing the decomposed resin again (hereinafter, this may be referred to as a chemically recycled polyester resin) can be suitably used.

[0023] The polyester resin recycled from the market or society, including PET bottles, used in the biaxially oriented polyester film of the present invention is mainly made of recycled containers mainly made of polyethylene terephthalate. For example, recycled beverage containers for tea drinks, soft drinks, etc. can be preferably used. They may be appropriately oriented, and are preferably colorless, but may contain a small amount of coloring components.

[0024] The recycled raw materials recycled from the market or society, including PET bottles, which can be preferably used, are polyesters manufactured and molded by normal polymerization and solid-phase polymerization, preferably mainly composed of polyethylene terephthalate, and may contain other polyester components and copolymer components. They may contain metal compounds such as antimony, germanium, and titanium as catalysts, and phosphorus compounds as stabilizers. Germanium is often used as a catalyst in polyesters for PET bottles, and if a film is made using recycled PET bottle raw materials, the film will contain 1 ppm or more of germanium. However, since it is only the catalyst content, it is usually 100 ppm or less, and usually 50 ppm or less.

[0025] Hereinafter, mechanically recycled polyester resin and chemically recycled polyester resin will be described.

[0026] [Mechanically recycled polyester resin] The collected used recycled PET bottles are sorted to avoid mixing with other materials or garbage, and after removing the labels, they are crushed into flakes. These flakes often contain foreign matter attached to them. In addition, it is possible that consumers fill used PET bottles with chemicals such as medicines and solvents and use them. For example, detergents for dishes, insecticides, herbicides, agricultural chemicals, and various oils are possible. Since normal washing cannot sufficiently remove the chemicals adsorbed on the surface of the PET bottles, it is preferable to perform alkaline washing. As the alkali metal hydroxide solution used in this washing process, a sodium hydroxide solution or a potassium hydroxide solution is used. In such a washing process, a preliminary washing may be performed before the alkaline washing. If alkaline washing is not performed, these will remain as foreign matter in the raw resin, which will not only cause contamination and lead to breakage during film production and reduce productivity, but will also remain as foreign matter in the film, affecting the appearance of the film and causing printing defects in the subsequent printing process.

[0027] The concentration of the aqueous solution of alkali metal hydroxide used in the washing step varies depending on the temperature, time, and stirring state, but is usually in the range of 1 to 10% by weight. The time required for washing is in the range of 10 to 100 minutes, and it is preferable to carry out the washing with stirring to enhance the effect.

[0028] It is preferable to perform rinsing and drying after the alkali washing. The alkali washing and rinsing may be repeated several times. If the aqueous solution of alkali metal hydroxide used in the washing in the alkali washing step remains in the flakes, the properties of the film finally obtained may be affected by the subsequent melt extrusion step in the pelletizing step or the melt extrusion step during film formation.

[0029] The sodium and potassium concentrations in the film finally obtained using polyester resins recycled from the market or society, including these PET bottles, are preferably greater than 0 ppm and less than 150 ppm, more preferably 3 to 120 ppm, and even more preferably 5 to 80 ppm. If the sodium or potassium concentration in the film is higher than 150 ppm, the film's heat resistance and thermal stability will decrease and it will become discolored, which is undesirable. If there is no sodium or potassium in the film, the effect of suppressing the production of diethylene glycol will be reduced, which is undesirable. In addition, polyester resins recycled from the market or society, including PET bottles, may contain a small amount of these components, and it is difficult to eliminate them completely.

[0030] In such a washing process, the PET bottle flakes are partially hydrolyzed by the aqueous solution of alkali metal hydroxide. In addition, the degree of polymerization of the resin decreases due to the heating during the molding of the PET bottles. Furthermore, after the collected PET bottles are crushed for reuse, the degree of polymerization decreases due to the influence of heat and moisture when melting and pelletizing again. They can be reused as they are, but depending on the application, if the degree of polymerization decreases, the moldability, strength, transparency, heat resistance, etc. may be deteriorated, and they may not be able to be reused as they are.

[0031] In such a case, in order to restore the reduced degree of polymerization, it is preferable to perform solid-state polymerization on the crushed and washed PET bottle flakes or on the flakes which have been melted and pelletized.

[0032] In the solid-state polymerization step, the washed flakes, or the flakes melt-extruded and pelletized, can be subjected to continuous solid-state polymerization in an inert gas such as nitrogen gas or a rare gas at 180 to 245°C, preferably 200 to 240°C.

[0033] It is desirable to adjust the flake or pellet conditions so that the final polyester resin recycled from the market or society, including PET bottles, has an intrinsic viscosity of 0.55 to 0.90 dl / g, preferably 0.60 to 0.85 dl / g.

[0034] The process for pelletizing the flakes will now be described. The flakes are melted, extruded, cooled, and pelletized using an extruder having a degassing means and a filtering means.

[0035] The melting step in the extruder can be carried out by melt kneading at a temperature of usually 260 to 300°C, preferably 265 to 295°C. The flakes obtained by crushing the PET bottles to be fed must be sufficiently dried, and it is preferable to dry them under conditions where the moisture content is 5 to 200, preferably 10 to 100 ppm, and further 15 to 50 ppm. If the flakes contain a large amount of moisture, a hydrolysis reaction will proceed in the melting step, and the intrinsic viscosity of the resulting polyester resin will decrease. As a degassing means, it is preferable to have at least one vacuum vent in the melting zone of the resin.

[0036] The extruder preferably has a filter as a filtering means capable of filtering out solid foreign matter having a particle size of 25 μm or more, preferably 15 μm or more, more preferably 10 μm or more, from the molten resin.

[0037] The molten resin that has passed through the filter passes through a die and is cooled in water, after which it is cut into pellets of the desired shape and granulated. [Polyester resin composition] The biaxially oriented polyester film of the present invention is made of a polyester resin composition containing the following polyester resin as a main component. The polyester resin constituting the biaxially oriented polyester film of the present invention is a polymer synthesized from a dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative. Examples include polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate, and polyethylene terephthalate is preferred from the viewpoints of mechanical properties, heat resistance, cost, etc. The term "main component" as used herein means that the content in the polyester resin composition is 80% by weight or more, preferably 90% by weight or more, more preferably 95% by weight or more, and most preferably 98% by weight or more.

[0038] In addition, these polyester resins may be copolymerized with other components as long as the object of the present invention is not impaired. Specifically, the copolymerization components include dicarboxylic acid components such as isophthalic acid, naphthalenedicarboxylic acid, 4,4-diphenyldicarboxylic acid, adipic acid, sebacic acid and their ester-forming derivatives. In addition, the diol components include diethylene glycol, hexamethylene glycol, neopentyl glycol, and cyclohexanedimethanol. In addition, polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol are also included. The copolymerization amount is preferably 10 mol% or less per constituent repeating unit, more preferably 5 mol% or less, and most preferably 3 mol% or less.

[0039] [Chemically recycled polyester resin] The method for producing the chemically recycled polyester resin used in the present invention is not particularly limited, but specifically, for example, as described in JP-A-2000-169623, collected used PET bottles are sorted, crushed, washed to remove foreign matter, and then depolymerized to decompose them into raw materials or intermediate raw materials for PET resin, which are then purified and polymerized to produce new PET resin. Depolymerization includes a method in which ethylene glycol (EG) is added in the presence of a catalyst to return the intermediate raw material in resin production to bis-2-hydroxyethyl terephthalate (BHET), which is an intermediate raw material, and then purified and repolymerized into PET, and a method in which polyethylene terephthalate is heated in a non-aqueous organic solvent in the presence of a catalyst containing oxidized iron as an essential component to produce terephthalic acid and ethylene glycol, which are then polymerized again, as described in JP-A-2000-302707. The characteristic of chemically recycled polyester resin is that foreign matter and other materials are removed during the depolymerization / repolymerization process, allowing it to be regenerated into a polyester resin of the same high quality as virgin resin. This makes it more hygienic than the mechanically recycled polyester resin described above, making it particularly suitable for use in food packaging.

[0040] The chemically recycled polyester resin used in the present invention is made from bales of compressed used PET bottles. These PET bottle bales are produced by known methods currently adopted by municipalities. Other polyethylene terephthalate waste or flakes of PET bottles can be used as starting materials instead of PET bottle bales.

[0041] A PET bottle bale made by compressing PET bottle waste to reduce its volume is placed in a crusher, and hot water, room temperature water, or hot water or room temperature water containing detergent is poured in to crush the PET bottles underwater.

[0042] Next, the mixture of flakes of PET bottles and washing water discharged from the crusher is immediately subjected to gravity separation to separate the metal, stone, glass, sand and flakes.The flakes are then separated from the washing water, rinsed with ion-exchanged water and centrifuged for dehydration.

[0043] The crude polyethylene terephthalate flakes obtained in the above pretreatment step are depolymerized, melted and simultaneously hydrolyzed to give a polyethylene terephthalate melt with a low degree of polymerization, which is then depolymerized with an excess of ethylene glycol to give a two-component mixed solution of crude BHET and crude ethylene glycol.

[0044] After the depolymerization reaction is completed, the temperature of the mixture of crude BHET and crude ethylene glycol is lowered and the mixture is filtered to remove unreacted linear and cyclic oligomers as high melting point precipitates, coagulation of remaining foreign plastics other than polyethylene terephthalate, and solid foreign matter such as metals. The mixture is then subjected to adsorption and ion exchange treatment to remove colored matter and dissolved ions, thereby removing the foreign matter contained in the crude BHET.

[0045] The mixed solution of crude BHET and crude ethylene glycol obtained through the pre-purification step is subjected to distillation and evaporation operations to separate and distill off ethylene glycol to obtain concentrated BHET, or the mixed solution of the two is cooled to 10°C or less to crystallize BHET, and then the ethylene glycol and BHET are subjected to solid-liquid separation to obtain concentrated BHET, and this concentrated BHET is evaporated in vacuum at a temperature of more than 190°C and not more than 250°C at a residence time of the concentrated BHET in an evaporator of 10 minutes or less to obtain purified bis-β-hydroxyethyl terephthalate.

[0046] After the high purity purified BHET is obtained as described above, the purified BHET is charged into a melt polycondensation reactor to obtain a high purity polyethylene terephthalate polymer.

[0047] Among the polyester resins constituting the biaxially oriented polyester film of the present invention, examples of a method for producing a polyester resin derived from a fossil fuel other than a mechanically recycled polyester resin or a chemically recycled polyester resin include a method in which the above-mentioned dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative are used as main starting materials, and the resulting polyester resin is then subjected to an esterification or ester exchange reaction according to a conventional method, and then subjected to a polycondensation reaction at high temperature and reduced pressure.

[0048] The intrinsic viscosity of the polyester resin constituting the biaxially oriented polyester film of the present invention is preferably in the range of 0.50 to 0.90 dl / g, more preferably 0.55 to 0.80 dl / g, from the viewpoints of film formability and recollection.

[0049] In order to ensure that the film roll obtained by winding up the biaxially oriented polyester film of the present invention satisfies all of the following requirements (1) to (4), the polyester resin composition of the present invention preferably contains at least one type of particles selected from the group consisting of inorganic particles, organic particles, and particles consisting of a mixture thereof. (1) The maximum projection height Sp of at least one of the film surfaces is 3.0 μm or less. (2) The haze at a film thickness of 12 μm is 10% or less. (3) The air escape time between the front and back surfaces of the film is 14 seconds or less. (4) When samples are taken every 1000 m in the longitudinal direction of the film from the surface of the film roll to the core, the variation in both the arithmetic mean height Sa and the maximum projection height Sp is 40% or less. (The variation is expressed by the following formula [1], where the maximum value is Xmax, the minimum value is Xmin, and the average value is Xave.) Variance (%) = 100 x (Xmax - Xmin) / Xave [1]

[0050] Examples of inorganic particles used include particles made of silica (silicon oxide), alumina (aluminum oxide), titanium dioxide, calcium carbonate, kaolin, crystalline glass filler, kaolin, talc, alumina, silica-alumina composite oxide particles, and barium sulfate. Examples of organic particles include acrylic resin particles, melamine resin particles, silicone resin particles, and particles made of crosslinked polystyrene. Among these, particles made of silica (silicon oxide), calcium carbonate, or alumina (aluminum oxide), or particles made of polymethacrylate, polymethyl acrylate, or derivatives thereof are preferred, and particles made of silica (silicon oxide) or calcium carbonate are more preferred, and among these, silica (silicon oxide) is particularly preferred in terms of reducing haze. These can provide transparency and slipperiness.

[0051] The weight average particle size of the particles in the present invention is a value measured by a call counter. The average particle size of the particles is preferably 0.5 to 4.0 μm, more preferably 0.8 to 3.8 μm, and further preferably 1.5 to 3.0 μm. If the weight-average particle size of the particles is less than 0.5 μm, the formation of surface irregularities will be insufficient, the slipperiness of the film will decrease, and the air entrained during winding onto a roll will not be uniformly removed, resulting in poor appearance such as wrinkles and pimples on the air bubbles, and the winding properties will be easily deteriorated. If the weight average particle size of the particles exceeds 4.0 μm, the formation of coarse protrusions tends to impair the quality of the film, such as causing printing defects, and the maximum protrusion height Sp on the surface of the biaxially oriented polyester film tends to exceed 3.0 μm.

[0052] The concentration of the inorganic particles in the particle-containing polyester resin composition (master batch) of the present invention is preferably from 2000 to 70000 ppm, more preferably from 5000 to 50000 ppm, and particularly preferably from 7000 to 30000 ppm. If the concentration of inorganic particles in the masterbatch is less than 2000 ppm, the additive ratio of the masterbatch containing inorganic particles will be large, and the ratio of polyester resin recycled from the market and society, including PET bottles as the main raw material, will be reduced, making it difficult to effectively obtain the resin characteristics of cheap resin and environmental friendliness, etc. If the concentration of inorganic particles in the masterbatch is more than 70000 ppm, the raw material ratio will fluctuate greatly in the longitudinal direction due to segregation of the raw material, and the obtained film will tend to have large variations in the longitudinal direction.

[0053] As a method for blending the particles in the polyester resin composition of the present invention, for example, the particles can be added at any stage of the esterification stage for producing the polyester resin, after the completion of the ester exchange reaction, or before the start of the polycondensation reaction. However, it is preferable to add the particles as a slurry dispersed in ethylene glycol or the like and then proceed with the polycondensation reaction. Also preferred is a method in which a slurry of particles dispersed in ethylene glycol or water or the like is blended with a polyester-based resin raw material using a vented kneading extruder, or a method in which dried particles are blended with a polyester-based resin raw material using a kneading extruder.

[0054] In the process of mixing the particles with the polyester-based resin raw material, it is preferable to minimize particle agglomerates in order to stably obtain the desired surface condition, but the influence of such agglomerates can be reduced by adjusting the conditions of the film-forming process of the biaxially oriented polyester film after the mixing process.

[0055] Furthermore, the polyester resin composition of the present invention may contain small amounts of other polymers, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, plasticizers, pigments, or other additives, within the scope of not impairing the object of the present invention.

[0056] When mechanically recycled polyester resin is used for the biaxially oriented polyester film obtained as described above, it is preferable that the content of isophthalic acid component is in the range of 0.01 mol% to 2.0 mol% based on 100 mol% of all dicarboxylic acid components in the film. In general, the crystallinity of polyesters used in PET bottles is controlled to improve the appearance of the bottles, and as a means for this, polyesters containing 10 mol% or less of isophthalic acid components are sometimes used. Therefore, when a mechanically recycled polyester resin recycled from PET bottles is used in the biaxially oriented polyester film of the present invention, a certain amount of material containing an isophthalic acid component will be contained.

[0057] The lower limit of the amount of isophthalic acid component in the total dicarboxylic acid components constituting the polyester resin contained in the film is preferably 0.01 mol%, more preferably 0.05 mol%, even more preferably 0.1 mol%, and particularly preferably 0.15 mol%. As mentioned above, polyester resins recycled from the market or society, including PET bottles, contain a large amount of isophthalic acid components, so if the isophthalic acid component constituting the polyester resin in the film is less than 0.01 mol%, it becomes difficult to manufacture a polyester film with a high ratio of recycled resin, which is not very preferable. The upper limit of the amount of isophthalic acid component in the total dicarboxylic acid components constituting the polyester resin contained in the film is preferably 2.0 mol%, more preferably 1.5 mol%, and even more preferably 1.0 mol%. If it exceeds 2.0 mol%, the crystallinity decreases, so the mechanical strength of the film may decrease, which is not very preferable. In addition, by setting the content of isophthalic acid component within the above range, it is easy to create a film with excellent lamination strength, heat shrinkage rate, and thickness unevenness, which is preferable.

[0058] The upper limit of the limiting viscosity of polyester resin recycled from the market or society, including PET bottles, is preferably 0.90 dl / g, more preferably 0.80 dl / g, further preferably 0.75 dl / g, and particularly preferably 0.69 dl / g. If it exceeds 0.90 dl / g, it may become difficult to extrude the resin from the extruder, lowering productivity, which is not preferable.

[0059] In the biaxially oriented polyester film of the present invention, the lower limit of the content of polyester resin recycled from the market or society, including PET bottles, relative to the total amount of polyester resin constituting the film is preferably 50% by weight, more preferably 70% by weight, even more preferably 90% by weight, and particularly preferably 100% by weight. If it is less than 50% by weight, the content is poor as a utilization of recycled resin, and it is not very preferable in terms of contribution to environmental protection. In addition, polyester resin recycled from the market or society, including PET bottles, can also be used as a master batch (high-concentration resin) used when adding lubricants and additives such as inorganic particles to improve the function of the film.

[0060] [Method of manufacturing biaxially oriented polyester film and film roll] The biaxially oriented polyester film of the present invention can be obtained by supplying and mixing polyester resin chips recycled from the market or society, including, for example, the above-mentioned PET bottles, and chips of a polyester resin composition mainly composed of polyester resin, to an extruder equipped with a hopper, melt-extruding the chips using the extruder to form an unstretched sheet, and stretching the unstretched sheet. Preferred examples are given below, but the present invention is not limited to these.

[0061] The biaxially oriented polyester film of the present invention may have a single layer, two layers, three layers, or a laminated structure of four or more layers. In the case of a two-layer or more layer structure, each layer contains the polyester resin, inorganic particles, and a resin other than the polyester resin as described above as constituent components, but the type or content of any of the constituent components of each adjacent layer is different. In the case of a single-layer structure, the surface layer (A) in the present invention corresponds to the entire biaxially oriented polyester film. In the case of a two-layer structure, the surface layer (A) in the present invention is one or both layers. In the case of a three-layer structure, the surface layer (A) in the present invention is one or both layers.

[0062] In the case of a three-layer structure, if the compositions constituting the film are represented as A, A', B, and C, the film can have a structure of, for example, A / B / C, A / B / A, or A / B / A', but if there is no need to change the surface characteristics of both sides, it is easier to manufacture and preferable to have an A / B / A structure in which both sides are designed to have the same composition. Here, A and A' do not have the same composition.

[0063] In particular, in the case of a three-layer structure, even if there are no inorganic particles in the base layer (B), the surface roughness of the film can be controlled by controlling the amount of added particles only in the surface layer (A), and the content of inorganic particles in the film can be reduced, which is preferable. This is because it also improves the problem of odor components escaping through voids (spaces) formed at the boundary between the inorganic particles and the polyester resin, which reduces the aroma retention. Furthermore, as long as it does not adversely affect the properties of the film surface, it is easy to mix and use recovered raw materials from the edges generated during the film production process or recycled raw materials from other film production processes in the base layer (B), which is also advantageous in terms of cost.

[0064] The lower limit of the particle content in the surface layer (A) of the biaxially oriented polyester film of the present invention is 600 ppm by weight, more preferably 700 ppm by weight, and particularly preferably 800 ppm by mass. If the particle content is less than 600 ppm by weight, the arithmetic mean height Sa of the film surface tends to be small, and the slipperiness may decrease, which is not preferable. In addition, the maximum protrusion height Sp of the film surface tends to be small, and the air entrained during winding into a roll is not uniformly removed, which tends to cause poor appearance such as wrinkles and acne on air bubbles, and the winding property tends to deteriorate.

[0065] When mixing the resin chips as raw materials, it is preferable to supply polyester resin chips recycled from the market or society, including PET bottles, from above to the hopper, and also supply chips of the polyester resin composition through a pipe (hereinafter sometimes referred to as an inner pipe) having an outlet directly above the extruder in the hopper, and mix and melt extrude both chips. If polyester resin chips recycled from the market or society, including PET bottles, and chips of the polyester resin composition are mixed and placed in a hopper above the extruder, resin chips with different specific gravities and chip shapes may cause raw material segregation in the hopper, and there is a high concern that raw material segregation will occur especially at the part where the inner wall of the hopper is not vertical (the part where it is oblique), but if the polyester resin composition is directly supplied to the upper part of the extruder in the hopper through the inner pipe, raw material segregation can be reduced even if the specific gravities and chip shapes are different, and polyester films can be stably industrially produced.

[0066] An example of a specific mixing procedure is shown in Figure 1. Figure 1 is a schematic diagram showing an example of the relationship between an extruder 2 equipped with a hopper 1 and an inner pipe 3. As shown in Figure 1, resins other than polyester resin chips recycled from the market or society, including PET bottles, which are the main raw material of the polyester film of the present invention, are supplied through the inner pipe 3, and chips of the polyester resin composition are supplied from the top of the hopper 1. And, since the outlet 4 of the inner pipe 3 is directly above the extruder (more precisely, directly above the resin supply port 5 of the extruder 2), the mixing ratio of the raw materials can be kept constant. By employing a means for directly feeding the polyester resin composition through this inner pipe to the portion immediately above the extruder in the hopper, it is possible to obtain the effect of suppressing variations in surface roughness.

[0067] When melt extruding polyester resin and polyester resin composition recycled from the market or society, including PET bottles, it is preferable to dry them using a dryer such as a hopper dryer or a paddle dryer, or a vacuum dryer. After drying the polyester resin and polyester resin composition recycled from the market or society, including PET bottles, in this way, an extruder is used to melt the polyester resin at a temperature of 200 to 300°C or higher, and extrude it into a film. Alternatively, the polyester resin, particles, and additives as necessary may be sent out by separate extruders, merged, mixed, melted, and extruded into a sheet. When extruding the molten resin composition, any existing method such as a T-die method or a tubular method can be used.

[0068] The extruded sheet-like molten polyester resin can be quenched to obtain an unoriented sheet. As a method for quenching the molten polyester resin, a method in which the molten polyester resin is cast onto a rotating drum from a die and quenched and solidified to obtain a substantially unoriented resin sheet can be suitably adopted. The temperature of the rotating drum is preferably set to 40° C. or lower.

[0069] Furthermore, the unstretched sheet obtained can be subjected to a combination of processes such as a biaxial stretching process in the longitudinal direction and the width direction, a heat setting process, and a heat relaxation process as described below to obtain the biaxially oriented polyester film of the present invention. The details are explained below. The longitudinal direction means the direction in which the unstretched sheet runs, and the width direction means the direction perpendicular thereto.

[0070] The stretching method may be simultaneous biaxial stretching, in which stretching in the longitudinal direction and the width direction is performed simultaneously, or sequential biaxial stretching, in which stretching in either the longitudinal direction or the width direction is performed first. However, sequential biaxial stretching is most preferred from the viewpoints of a fast film-forming speed and high productivity, and of excellent thickness uniformity of the finally obtained biaxially oriented polyester film. The film-forming speed referred to here means the running speed (m / min) of the biaxially oriented polyester film when it is taken up around a master roll after the stretching step.

[0071] The temperature during stretching of the unstretched sheet in the longitudinal direction is preferably in the range of (Tg+15) to (Tg+55)°C, using the glass transition temperature (hereinafter, Tg) of the polyester resin as an index, and the stretching ratio is preferably in the range of 4.2 to 4.7 times. When the stretching temperature is (Tg+55)°C or lower and 4.2 times or higher, the maximum projection height Sp is easily controlled to be equal to or lower than the upper limit of (1) above, the molecular orientation in the longitudinal direction and the width direction is well balanced, and the difference in physical properties between the longitudinal direction and the width direction is small, which is preferable. In addition, the flatness of the obtained biaxially stretched polyester film is also good, which is preferable. On the other hand, when the longitudinal stretching temperature is (Tg+15)°C or higher and the stretching ratio is 4.7 times or less, the maximum projection height Sp is easily controlled to be equal to or less than the upper limit of (1) above. This is preferable because the tensile stress (bowing phenomenon) generated in the direction opposite to the running direction of the film in the thermal relaxation step does not become too large.

[0072] In addition, in the longitudinal stretching, a method of stretching between a plurality of rolls in two, three, or four or more stages, rather than in one stage, is preferred because it allows the stretching ratio in the longitudinal direction to be increased without increasing the stretching speed too much, and therefore makes it possible to further reduce the difference in physical properties in the width direction of the film. Two-stage or three-stage stretching is preferred from the viewpoints of effect, equipment, and cost. Furthermore, in the longitudinal stretching, by stretching at low magnifications in the first and second stages, it is possible to form a large number of polymer structures that are weakly oriented in the longitudinal direction without crystallization, and by further stretching the film at a high magnification in the third stage, the polymer structures are strongly oriented in the longitudinal direction and the stretching stress during stretching increases, making it easier to control the occurrence of coarse protrusions due to particle aggregation and making it easy to keep the maximum protrusion height Sp on the film surface below the above-mentioned upper limit value.

[0073] The film obtained by stretching the unstretched sheet in the longitudinal direction may be subjected to a surface treatment such as corona treatment or plasma treatment as necessary, and then a resin dispersion or resin solution may be applied to at least one surface of the film to impart functions such as easy slippage, easy adhesion, and antistatic properties.

[0074] When the film obtained by stretching an unstretched sheet in the longitudinal direction is to be stretched in the width direction, the film is introduced into a tenter device, both ends of the film obtained by stretching the unstretched sheet in the longitudinal direction are held with clips, and the film is heated to a predetermined temperature with hot air. After that, the film is transported in the longitudinal direction while the distance between the clips is increased, thereby stretching the film in the width direction. If the temperature during stretching in the width direction is Tg+5° C. or higher, breakage during stretching is less likely to occur, which is preferable. In addition, when the stretching temperature is Tg+40° C. or lower, uniform stretching in the width direction is facilitated, and unevenness in thickness in the width direction is less likely to occur, which is preferable since it reduces variation in the winding hardness of the film roll surface in the width direction. It is more preferably Tg+8°C or higher and Tg+37°C or lower, and even more preferably Tg+11°C or higher and Tg+34°C or lower. The stretching ratio in the width direction of the film obtained by stretching the unstretched sheet in the machine direction is preferably 4.0 times or more and 6 times or less. When the stretching ratio in the width direction is 4.0 times or more, a high yield is easily obtained in terms of material balance, the mechanical strength is not decreased, thickness unevenness in the width direction is not increased, and the winding hardness in the width direction of the film roll is not easily varied, which is preferable. The stretching ratio in the width direction is more preferably 4.1 times or more, and even more preferably 4.2 times or more. In addition, if the stretching ratio in the transverse direction is 6.0 times or less, the film is less likely to break during stretching and is therefore preferable.

[0075] The widthwise stretching step is followed by a heat setting step. The heat setting temperature of the film obtained by stretching the unstretched sheet in the machine direction and then stretching the film in the width direction is preferably 240° C. or higher and 250° C. or lower. When the heat setting temperature is 240° C. or higher, the heat shrinkage rate in both the longitudinal and transverse directions is not too high, and the thermal dimensional stability during secondary processing is improved, which is preferable. On the other hand, when the heat setting temperature is 250° C. or less, bowing is less likely to increase, which is preferable.

[0076] A heat relaxation treatment step is then carried out, which may be carried out separately from the heat setting step after the heat setting step, or may be carried out simultaneously with the heat setting step. The relaxation rate in the film width direction in the heat relaxation treatment step is preferably 4% or more and 8% or less. When the relaxation rate is 4% or more, the heat shrinkage rate in the width direction of the obtained biaxially oriented polyester film is not too high, and the dimensional stability during secondary processing is good, which is preferable. On the other hand, when the relaxation rate is 8% or less, the tensile stress (bowing phenomenon) generated in the opposite direction to the running direction of the film at the center of the film in the width direction does not become too large, and the rate of variation in the film thickness in the width direction does not become large, which is preferable.

[0077] In the heat relaxation treatment step, the film obtained by stretching the unstretched sheet in the longitudinal direction is stretched in the width direction, and during the time until the film is shrunk by heat relaxation, the restraining force in the width direction decreases and the film slackens under its own weight. In addition, the film may expand due to the accompanying air currents of hot air blown out from nozzles installed above and below the film. As a result, the film is in a state in which it is very susceptible to vertical fluctuations, and the amount of change in the orientation angle and the oblique heat shrinkage difference of the obtained biaxially stretched polyester film is likely to vary greatly. Methods for reducing these problems include, for example, adjusting the speed of the hot air blown from the upper and lower nozzles to keep the film parallel.

[0078] The biaxially oriented polyester film of the present invention may be subjected to corona discharge treatment, glow discharge treatment, flame treatment, surface roughening treatment, and may also be subjected to known anchor coat treatment, printing, decoration, etc., as long as the object of the present invention is not impaired.

[0079] The wide biaxially oriented polyester film stretched by the above method is wound up by a winder device to produce a master roll. The width of the master roll is preferably 5000 mm or more and 10000 mm or less. If the roll width is 5000 mm or more, the cost per film area in the subsequent slitting process, deposition processing and printing processing is lower, which is preferable. The length of the master roll is preferably 10,000 m or more and 100,000 m or less. If the length of the roll is 5,000 m or more, the cost per film area in the subsequent secondary processing such as slitting, deposition processing, and printing processing is preferably low. The winding width of the film roll slit from the master roll is preferably 400 mm or more and 3000 mm or less. If the winding width is 400 mm or more, the time and effort required for frequent film roll replacement during the printing process is reduced, which is preferable in terms of cost. In addition, the winding width is preferably longer, but if it is 3000 mm or less, the roll width is not too large and the roll weight is not too heavy, which is preferable since handling properties are not reduced. The length of the film roll is preferably 2000 m or more and 65000 m or less. If the length is 2000 m or more, the time and effort required for frequently replacing the film roll during the printing process is reduced, which is preferable in terms of cost. In addition, the longer the length, the better, but if the length is 65000 m or less, the roll diameter will not be too large and the roll weight will not be too heavy, which is preferable since handling properties will not be reduced. The core used for the film roll is not particularly limited, and typically, a cylindrical core made of plastic, metal, or cardboard with a diameter of 3 inches (37.6 mm), 6 inches (152.2 mm), 8 inches (203.2 mm), etc. can be used.

[0080] [Characteristics of biaxially oriented polyester film and film roll] The film roll obtained by winding up the biaxially oriented polyester film made of a polyester resin composition containing polyester resin and particles recycled from the market or society, including the PET bottle of the present invention, preferably satisfies all of the following requirements (1) to (4). Each of these will be described in detail. (1) The maximum projection height Sp of at least one of the film surfaces is 3.0 μm or less. (2) The haze at a film thickness of 12 μm is 10% or less. (3) The air escape time between the front and back surfaces of the film is 14 seconds or less. (4) When samples are taken every 1,000 m in the longitudinal direction of the film from the surface of the film roll to the core, the variation in both the arithmetic mean height Sa and the maximum projection height Sp is 40% or less. (The variation is expressed by the following formula [1], where the maximum value is Xmax, the minimum value is Xmin, and the average value is Xave. Variance (%) = 100 x (Xmax - Xmin) / Xave [1]

[0081] (Maximum projection height Sp) The maximum projection height Sp of at least one surface of the biaxially oriented polyester film of the present invention is preferably 3.0 μm or less, more preferably 2.5 μm or less, and even more preferably 2.0 μm or less. If the maximum projection height Sp is 3.0 μm or less, the formation of coarse projections can cause printing defects, such as poor print appearance and poor design, which is less likely to impair the film quality, and is therefore preferable. If the variation in the longitudinal arithmetic mean height Sa and the maximum projection height Sp of the film roll exceeds 40%, there is a risk that the quality of the packaging material produced by secondary processing the biaxially oriented polyester film roll will vary. The arithmetic mean height Sa of at least one surface of the biaxially oriented polyester film of the present invention is preferably 0.10 μm or less, more preferably 0.07 μm or less, and even more preferably 0.05 μm or less. If the arithmetic mean height Sa exceeds 0.10 μm or less, there is a risk of impairing the film quality, such as poor print appearance and poor design due to printing voids.

[0082] (Hayes) The haze of the biaxially oriented polyester film of the present invention at a film thickness of 12 μm is 10% or less, more preferably 5% or less, and even more preferably 4% or less. If the haze at a film thickness of 12 μm exceeds 10%, the print appearance deteriorates and it becomes difficult to detect foreign matter during high-speed processing, making it difficult to obtain sufficient quality.

[0083] (Air release time) The air escape time between the front and back surfaces of the biaxially oriented polyester film of the present invention is preferably 14 seconds or less, more preferably 13 seconds or less, even more preferably 12 seconds or less, and particularly preferably 10 seconds or less. If the air escape time exceeds 14 seconds, the air wound into the roll is not uniformly escaped during the production process and when the film is wound into a roll by rewinding, slitting, etc., which is likely to cause poor appearance such as wrinkles and air bubble-like acne.

[0084] (Kinematic friction coefficient) The dynamic friction coefficient between one surface of the biaxially oriented polyester film of the present invention and the opposite surface thereof is preferably 0.20 or more and 0.60 or less. When the ratio is 0.20 or more, the films do not slide too much against each other, and wrinkles are unlikely to occur in the film roll when the film roll is wound by a winder device during film production or slitting, and secondary processability is unlikely to decrease. Furthermore, if the ratio is 0.60 or less, the films slide against each other, so that when the film roll is wound by a winder device during film production or slitting, the film roll is less likely to be misaligned, and secondary processability is less likely to deteriorate. It is further preferably 0.50 or less, and most preferably 0.45 or less.

[0085] (Static friction coefficient) The static friction coefficient between one surface of the biaxially oriented polyester film of the present invention and the opposite surface thereof is preferably 0.20 or more and 0.60 or less. When the ratio is 0.20 or more, the films do not slide too much against each other, and wrinkles are unlikely to occur in the film roll when the film roll is wound by a winder device during film production or slitting, and secondary processability is unlikely to decrease. Furthermore, if the ratio is 0.60 or less, the films slide against each other, so that when the film roll is wound by a winder device during film production or slitting, the film roll is less likely to be misaligned, and secondary processability is less likely to deteriorate. It is further preferably 0.50 or less, and most preferably 0.45 or less.

[0086] (Inorganic particle content) The content of inorganic particles in all layers of the biaxially oriented polyester film of the present invention is preferably 100 ppm or more and 1000 ppm or less, more preferably 800 ppm or less. If the content of inorganic particles is less than 100 ppm, the slipperiness is reduced, which causes problems during roll running, winding, rewinding, slitting, etc. during the film manufacturing process, and is likely to cause scratches on the film surface, winding wrinkles, and static electricity. If the content of inorganic particles exceeds 1000 ppm, the arithmetic mean height Sa and maximum protrusion height Sp of the film surface tend to be high, so care must be taken. In addition, the number of voids in the film increases, which is likely to cause a decrease in transparency.

[0087] (film thickness) The film thickness of the biaxially oriented polyester film of the present invention is preferably 5 to 40 μm. If it is 5 μm or more, the strength and stiffness of the film will not decrease, and the film roll is less likely to wrinkle when wound by a winder device, which is preferable. On the other hand, if the film thickness is in the range of 40 μm or less, sufficient strength and stiffness can be obtained, and it is preferable to make the film thinner from the viewpoint of cost. The film thickness is more preferably 8 to 30 μm, and particularly preferably 9 to 20 μm.

[0088] (Number of defects) The biaxially oriented polyester film of the present invention is 2 From the viewpoint of film quality, it is preferable that there are fewer than 20 foreign objects measuring 1 mm or more per film, and the film can be said to be of high quality even though it is made from recycled polyester raw materials. EXAMPLES

[0089] A. The evaluation method for polyester resin is as follows. [Glass transition temperature (Tg)] Using a differential scanning calorimeter (DSC6220, manufactured by SII NanoTechnology Inc.), 5 mg of the resin sample was melted to 280°C under a nitrogen atmosphere, held for 5 minutes, and then rapidly cooled with liquid nitrogen. Measurements were performed at a heating rate of 20°C / min from room temperature.

[0090] [Intrinsic viscosity (IV)] 0.2 g of polyester resin was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (weight ratio)), and the viscosity was measured using an Ostwald viscometer at 30° C. The unit is dl / g.

[0091] [Content of terephthalic acid and isophthalic acid components in raw polyester and polyester that composes the film] A sample solution was prepared by dissolving chloroform D (Eurisop) and trifluoroacetic acid D1 (Eurisop) in a mixed solvent at a volume ratio of 10:1, and the NMR of the protons in the sample solution was measured using an NMR (GEMINI-200; Varian) at a temperature of 23°C and an accumulation of 64 times. In the NMR measurement, the peak intensity of a specified proton was calculated, and the content (mol %) of the terephthalic acid component and the isophthalic acid component in 100 mol % of the acid component was calculated.

[0092] B. The polyester film was evaluated as follows. Sampling of films for evaluation of properties other than the foreign matter in the film (number of defects), the wrinkle evaluation of the film roll, and the variation (%) of the arithmetic mean height Sa and the maximum protrusion height Sp in the film, was performed from the surface layer of the biaxially oriented polyester film roll of the present invention.

[0093] [Film thickness] The measurement was performed using a dial gauge in accordance with JIS K7130-1999 Method A.

[0094] [Hayes] According to JIS-K7136, a piece measuring 5 cm in the longitudinal direction and 5 cm in the transverse direction was cut out from the obtained film, and the haze was measured using a haze meter (NDH5000) manufactured by Nippon Denshoku Industries Co., Ltd. The measurement was carried out three times, and the average value was calculated.

[0095] [Arithmetic mean height Sa, maximum height Sp] In accordance with ISO25178, a piece measuring 10cm in the longitudinal direction and 10cm in the transverse direction was cut from the obtained film, and scanned using a Zygo white laser interferometer (NEW VIEW8300) under the following observation conditions to measure the arithmetic mean height Sa (μm) and maximum projection height Sp (μm). The measurement was performed on the surface excluding foreign matter such as unmelted material and dust. Measurements were taken at 10 randomly selected points on a 10 cm x 10 cm sample, and the average values ​​were taken as the arithmetic mean height Sa and the maximum projection height Sp, respectively. The variation (%) of the arithmetic mean height Sa and the maximum projection height Sp was measured by sampling the obtained polyester film roll (width 800 mm, roll length 30,000 m) in the longitudinal direction from the surface layer of the film roll to the core every 1000 m. Measurements were performed on each sampled film under the above conditions. The maximum value of the obtained arithmetic mean height Sa was designated Xmax(N), the minimum value was designated Xmin(N), and the average value was designated Xave, and the variation in the longitudinal direction was calculated using the formula [1]. (Observation conditions) Objective lens: 10x Zoom lens: 1x Field of view: 0.82 x 0.82 mm Sampling interval: 0.803μm Estimated measurement time: 4 seconds Type: Surface Mode: CSI Z resolution: High Scan length: 20μm Camera mode: 1024×1024@100Hz Shutter speed: 100% Light output: 1.3% Option: SureScan Off SmartPsi Averages 4 Noise Reduction Signal processing option: Fringe order analysis Advanced Fringe removal ON

[0096] [Kinematic friction coefficient, static friction coefficient,] The obtained film was cut into a piece measuring 400 mm in length and 100 mm in width to prepare a sample film. This was aged for 12 hours in an atmosphere of 23°C and 65% RH, and then divided into a test piece measuring 300 mm in length and 100 mm in width for the test table and a test piece measuring 100 mm in length and 100 mm in width for the sliding piece. The test piece for the test table was set on the test table, and the test piece for the sliding piece was the bottom surface (area size 39.7 mm2) of a metal sliding piece with a load of 1.5 kg. 2 , square) so that each side was touching the other. In accordance with JIS K-7125, a tensile testing machine (Tensilon RTG-1210 manufactured by A&D Corporation) was used to measure the dynamic friction coefficient and static friction coefficient of the test piece at a sliding speed of 200 mm / min, at 23°C and 65% RH, and the average of three measurements was used.

[0097] [Foreign matter in film (number of defects)] A film roll with a width of 800 mm and a length of 10,000 m (8,000 square meters) was rewound using a rewinding machine. During rewinding, the number of defects was checked using a FUTEC defect detector (model F MAX MR). The number of defects 1 mm or larger in either the vertical or horizontal direction was counted. The number of defects per 1,000 square meters was calculated from the total number of defects using the following formula [3]. Number of defects per 100 square meters = total number of defects / 80... [3] The number of foreign matters in the film was measured and evaluated according to the following criteria. ○: Number of foreign objects in the film: 20 / 100m 2 less than ×: Number of foreign objects in the film: 20 / 100m 2 End

[0098] [Content of inorganic particles in all layers of film] The obtained film was analyzed by a fluorescent X-ray analyzer (Rigaku Corporation, Supermini 200 model) using a previously obtained calibration curve.

[0099] [Air release time] As shown in Figure 3, film 4 is placed on base plate 1. Next, film holder 2 is placed on top of film 4 and fixed in place to apply tension to film 4. Next, film 5 is placed on top of film holder 2 with the side opposite to the top surface of film 4 placed on base plate 1 facing down. Next, film holder 8 is placed on top of film 5, and the film holders 8, 2 and base plate 1 are fixed in place using screws 3. Next, cavity 2a in film holder 2 is connected to vacuum pump 6 via small hole 2c in film holder 2 and pipe 7. When vacuum pump 6 is driven, film 5 is sucked into cavity 2a and tension is applied to it. At the same time, the pressure in the overlapping surfaces of films 4 and 5 is reduced via small hole 2d provided circumferentially in film holder 2, and films 4 and 5 begin to adhere to each other from the outer periphery at their overlapping surfaces. The state of adhesion can be easily confirmed by observing the interference fringes from above the overlapping surfaces. Then, the time (seconds) from when interference fringes appear on the periphery of the overlapping surfaces of films 4 and 5 until they spread to the front of the overlapping surfaces and stop moving is measured, and this time (seconds) is taken as the air release time. The measurement is repeated five times by replacing the two films, and the average value is used.

[0100] [Evaluation of wrinkles on film rolls] The formed biaxially oriented polyester film was wound up to a width of 800 mm and a length of 12,000 m, and the wrinkles on the surface layer of the roll were visually evaluated according to the following criteria. ○: No wrinkles △: There are slight wrinkles, but the wrinkles disappear when a tension of about 20 N / m is applied to the pulled-out film. ×: There are strong wrinkles, and the wrinkles do not disappear even when a tension of about 20 N / m is applied to the pulled-out film.

[0101] Details of the raw resin chips used in the present examples and comparative examples are given below. (Polyester resin A): Mechanically recycled polyester resin The mechanically recycled polyester resin recycled from PET bottles used in the production of the biaxially oriented polyester film described below was synthesized by the following method. After washing out the remaining beverage and other foreign matter from the PET bottle, the bottle was crushed to obtain flakes. The obtained flakes were washed with 3.5% by weight of sodium hydroxide solution under stirring at a flake concentration of 10% by weight, 85°C, and 30 minutes. After the alkaline washing, the flakes were taken out and washed with distilled water under stirring at a flake concentration of 10% by weight, 25°C, and 20 minutes. This water washing was repeated two more times by replacing the distilled water. After washing with water, the flakes were dried, melted in an extruder, and filtered out finer foreign matter twice using filters with successively smaller opening sizes, and filtered out the finer foreign matter with a filter with the smallest opening size of 50 μm for the third time to obtain polyester resin A with an intrinsic viscosity of 0.69 dl / g and an isophthalic acid content of 1.5 mol%.

[0102] (Polyester resin B): Mechanically recycled polyester resin Polyester resin B having an intrinsic viscosity of 0.69 dl / g and an isophthalic acid content of 1.5 mol % was obtained in the same manner as in the production process of polyester resin A, except that alkali washing was not carried out.

[0103] (Polyester resin C): Chemically recycled polyester resin The chemically recycled polyester resin recycled from PET bottles used in the production of the biaxially oriented polyester film described below was synthesized by the following method. The PET bottles that were collected and sorted were put into a wet grinder, and 1,000 liters of water with 500g of liquid kitchen detergent added was circulated inside the wet grinder while grinding, and metals, sand, glass, and other materials with high specific gravity were precipitated in a gravity separator connected to the grinder, and flakes were taken out from the top layer. These flakes were rinsed with pure water and centrifuged to produce recovered flakes.

[0104] The recovered flakes were melted in a wet state, and 30 kg of the melted flakes were placed in a stirrer-equipped autoclave and charged into a preheated mixture of 150 kg of ethylene glycol and 150 g of zinc acetate dihydrate. After removing fractions with a boiling point lower than that of ethylene glycol, such as water and acetic acid, the mixture was reacted for 4 hours at a temperature of 195-200°C using a reflux condenser.

[0105] After the reaction was completed, the temperature of the contents of the reactor was lowered to 97 to 98° C., and the contents were filtered while still hot to remove suspended matter and precipitates.

[0106] The filtrate after hot filtration was further cooled, and after confirming that the crude BHET was completely dissolved, it was passed through an activated carbon bed at 50 to 51°C and then through an anion / cation exchange mixed bed over 30 minutes for pre-purification treatment.

[0107] The above pre-purified liquid was again charged into the stirring autoclave and heated to distill off excess ethylene glycol at 198°C under normal pressure, to obtain a molten liquid of concentrated BHET.

[0108] The resulting molten liquid of concentrated BHET was allowed to cool naturally while stirring under a nitrogen gas atmosphere, and then removed from the autoclave to obtain a small block of concentrated BHET.

[0109] The block of fine pieces was again heated to 130°C and melted, then fed to a thin-film vacuum evaporator by a metering pump, evaporated, and cooled and condensed to obtain purified BHET.

[0110] This purified BHET was used as a raw material to carry out melt polymerization, thereby obtaining a chemically recycled polyester resin C having an intrinsic viscosity of 0.696 dl / g.

[0111] (Polyester Resin D) The fossil fuel-derived PET resin used in the production of the biaxially oriented polyester film described below was terephthalic acid / ethylene glycol=100 / / 100 (mol %) (manufactured by Toyobo Co., Ltd., intrinsic viscosity 0.62 dl / g).

[0112] (Polyester Resin E) When the temperature of the esterification reactor reached 200°C, a slurry consisting of terephthalic acid [86.4 parts by mass] and ethylene glycol [64.4 parts by mass] was charged, and antimony trioxide [0.017 parts by mass] and triethylamine [0.16 parts by mass] were added as catalysts while stirring. The reactor was then heated to increase the temperature, and a pressurized esterification reaction was carried out under conditions of a gauge pressure of 0.34 MPa and 240°C. Thereafter, the inside of the esterification reactor was returned to normal pressure, and magnesium acetate tetrahydrate [0.071 parts by mass] was added, followed by trimethyl phosphate [0.014 parts by mass]. After the temperature was raised to 260°C over 15 minutes, trimethyl phosphate [0.012 parts by mass] was added, followed by sodium acetate [0.0036 parts by mass]. After 15 minutes, dispersion was performed using a high-pressure disperser, and 0.7 parts by weight of ethylene glycol slurry of amorphous silica particles with an average particle size of 2.5 μm was added based on the particle content. These silica particles were obtained by previously preparing an ethylene glycol slurry, centrifuging the slurry to remove 35% of the coarse particles, and then filtering the slurry using a metal filter with an opening of 5 μm. After 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reactor, and polycondensation was performed under reduced pressure at 280°C to obtain a polyester resin E with an intrinsic viscosity of 0.62 dl / g.

[0113] (Polyester resins F, G, H, I, J) Polyester resins F, G, H, I and J were obtained in the same manner as for polyester resin D, except that the weight average particle size and particle content of the silica particles were changed.

[0114] The raw resin chips are as shown in Table 1. The abbreviations in the table are as follows: TPA: Terephthalic acid EG: Ethylene glycol

[0115] [Table 1]

[0116] [Example 1] A three-layer film was produced using three extruders. The base layer (B) was 95.0 mass% polyester resin A and 5.0 mass% polyester resin D, and the surface layer (A) was 87.5 mass% polyester resin A and 12.5 mass% polyester resin D. Here, polyester resin D was introduced using an inner pipe as shown in Figure 1 so that it was mixed with other raw materials before entering the extruder. After drying each of the raw resins, the mixed resin forming the surface layer (A) was melt-extruded from the first and third extruders at a resin temperature of 285°C, and the mixed resin forming the base layer (B) was melted from the second extruder at a resin temperature of 285°C. The layers were then merged and laminated in a T-die in the order of surface layer (A) / base layer (B) / surface layer (A) from the side contacting the casting drum so that the thickness ratio was 1 / 10 / 1 (μm), extruded from a T-shaped nozzle, and cooled and solidified on a casting drum with a surface temperature of 30°C to obtain an unstretched polyethylene terephthalate sheet. At this time, static electricity was applied using a wire electrode having a diameter of 0.15 mm, and the film was brought into close contact with a cooling drum to obtain a three-layer unstretched film. The obtained unstretched film was heated to 115°C and stretched in the longitudinal direction at a total stretch ratio of 4.5 times in three stages, 1.24 times in the first stage, 1.4 times in the second stage, and 2.6 times in the third stage. The film was then stretched in the width direction at a temperature of 140°C and a stretch ratio of 4.3 times, heat-set at 245°C, and heat-relaxed by 5% in the width direction. The surface layer (A) on the side that came into contact with the chill roll was then stretched at 40 W·min / m 2 A corona treatment was performed under the above conditions, and the film was wound up into a roll using a winder to produce a master roll (30,000 m in length, 8,000 mm in width) of biaxially oriented polyester film with a thickness of 12 μm. The biaxially oriented polyester film was unwound from the obtained master roll and slit into a width of 800 mm onto a core having a diameter of 6 inches (152.2 mm). The film roll was wound up while applying surface pressure to the film roll with a contact roll and tension to the film with a two-axis turret winder. The raw material composition and film-forming conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface layer (A) on the side in contact with the chill roll.

[0117] [Example 2] As raw materials, the surface layer (A) had 64.0% by mass of polyester resin A and 36.0% by mass of polyester resin E, the base layer (B) had 64.0% by mass of polyester resin A and 36.0% by mass of polyester resin E, and the thickness ratio in the T-die was changed to 3 / 6 / 3 (μm). A biaxially stretched film was produced in the same manner as in Example 1 to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, the physical properties of the obtained film, and the evaluation results are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0118] [Example 3] A biaxially stretched film was produced in the same manner as in Example 1, except that the raw materials were changed to 78.0% by mass of polyester resin A and 22.0% by mass of polyester resin F in the surface layer (A), and 98.0% by mass of polyester resin A and 2.0% by mass of polyester resin F in the base layer (B), to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, the physical properties of the obtained film, and the evaluation results are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0119] [Example 4] A biaxially stretched film was produced in the same manner as in Example 1, except that the raw materials were changed to 83.5% by mass of polyester resin A and 16.5% by mass of polyester resin G in the surface layer (A), and 100.0% by mass of polyester resin A in the base layer (B), to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0120] [Example 5] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resin of the surface layer (A) was changed to polyester resin B as the raw material, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that came into contact with the chill roll.

[0121] [Example 6] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resin A used in the surface layer (A) and base layer (B) in Example 1 was changed to polyester resin C as the raw material, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that came into contact with the chill roll.

[0122] [Example 7] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resin A used in the surface layer (A) and base layer (B) in Example 1 was changed to a ratio of polyester resin A / polyester resin C = 50 / 50 as the raw material, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, and the physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0123] [Example 8] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resin A used in the surface layer (A) and base layer (B) in Example 1 was changed to a ratio of polyester resin A / polyester resin C = 10 / 90, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0124] [Example 9] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resins of the surface layer (A) and base layer (B) were changed to a ratio of polyester resin C / polyester resin D = 50 / 50 as the raw materials, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0125] [Example 10] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resin of the surface layer (A) was changed to a mixture of 90% by weight of polyester resin C and 10% by weight of polyester resin D, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that came into contact with the chill roll.

[0126] [Comparative Example 1] A biaxially stretched film was produced in the same manner as in Example 1, except that the polyester resin of the surface layer (A) was changed to polyester resin D as the raw material, to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that came into contact with the chill roll.

[0127] [Comparative Example 2] A biaxially stretched film was produced in the same manner as in Example 1, except that the raw materials were changed to 82.0 mass% polyester resin A and 18.0 mass% polyester resin I for the surface layer (A), and 98.6 mass% polyester resin A and 1.4 mass% polyester resin I for the base layer (B), to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, and the physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0128] [Comparative Example 3] A biaxially stretched film was produced in the same manner as in Example 1, except that the raw materials were changed to 96.0% by mass of polyester resin A and 4.0% by mass of polyester resin J in the surface layer (A) and base layer (B), to obtain a biaxially oriented polyester film having a thickness of 12 μm. The raw material composition and film production conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film, are shown in Table 2. The film was evaluated on the surface layer (A) on the side that contacted the chill roll.

[0129] [Comparative Example 4] As in Example 1, a three-layer film was produced using three extruders. The base layer (B) contained 95.0% by mass of polyester resin A and 5.0% by mass of polyester resin E, and the surface layer (A) contained 87.5% by mass of polyester resin A and 12.5% ​​by mass of polyester resin E. However, polyester resin A and polyester resin E were all mixed together and fed into the extruder. In other words, polyester resin E was mixed at the top of the hopper and fed into the extruder without using an inner pipe. After drying each raw material resin, the mixed resin forming the surface layer (A) was melt-extruded from the first and third extruders at a resin temperature of 285°C, and the mixed resin forming the base layer (B) was melted from the second extruder at a resin temperature of 285°C, and the layers were laminated in a T-die in the order of surface layer (A) / base layer (B) / surface layer (A) from the side contacting the casting drum so that the thickness ratio was 1 / 10 / 1 (μm), extruded from a T-shaped die, and cooled and solidified on a casting drum with a surface temperature of 30°C to obtain an unstretched polyethylene terephthalate sheet. At that time, static electricity was applied using a wire-shaped electrode with a diameter of 0.15 mm, and the film was adhered to the cooling drum to obtain a three-layer unstretched film. The obtained unstretched film was heated to 115°C and stretched in the longitudinal direction at a total stretch ratio of 4.5 times in three stages, 1.24 times in the first stage, 1.4 times in the second stage, and 2.6 times in the third stage. The film was then stretched in the width direction at a temperature of 140°C and a stretch ratio of 4.3 times, heat-set at 245°C, and heat-relaxed by 5% in the width direction. The surface layer (A) on the side that came into contact with the chill roll was then stretched at 40 W·min / m 2A corona treatment was performed under the above conditions, and the film was wound up into a roll using a winder to produce a master roll (30,000 m in length, 8,000 mm in width) of biaxially oriented polyester film with a thickness of 12 μm. The biaxially oriented polyester film was unwound from the obtained master roll and slit into a width of 800 mm onto a core having a diameter of 6 inches (152.2 mm). The film roll was wound up while applying surface pressure to the film roll with a contact roll and tension to the film with a two-axis turret winder. The raw material composition and film-forming conditions of the obtained film, as well as the physical properties and evaluation results of the obtained film are shown in Table 2. The film was evaluated on the surface layer (A) on the side in contact with the chill roll.

[0130] As shown in the results of Table 2, the films of Examples 1 to 10 had maximum projection height Sp, haze, air escape time, and longitudinal variation within the specified ranges, and therefore had excellent transparency and mechanical properties, as well as excellent slip properties and winding properties during the film manufacturing process. Furthermore, by using polyester resin recycled from the market and society, including PET bottles, these are environmentally friendly polyester films, with little foreign matter and little variation in longitudinal physical properties even in long film rolls with a long wound length.

[0131] In Comparative Example 1, the maximum projection height Sp, haze, air release time, and longitudinal variation of the obtained film were within the specified ranges, and therefore the film had excellent transparency and mechanical properties, as well as excellent slip properties and winding properties during the film production process. However, since the film was made of a conventional polyester resin derived from fossil fuels, it was inferior as an environmentally friendly polyester film.

[0132] In Comparative Example 2, the haze, air release time, and longitudinal variation of the obtained film were within the ranges, but the maximum projection height Sp was large, and therefore the film had poor smoothness.

[0133] In Comparative Example 3, the maximum projection height Sp, haze, air escape time, and longitudinal variation of the obtained film were within the range, but the air escape time was long, so the air wound into the roll was not escaped uniformly, and the roll wrinkle evaluation was poor.

[0134] In Example 5, the maximum projection height Sp, haze, air escape time, and longitudinal variation of the obtained film were within the specified ranges, and therefore the film had excellent transparency and mechanical properties, as well as excellent slip properties and winding properties during the film production process. However, since polyester resin recycled from the market and society, including PET bottles that had not been subjected to alkaline cleaning, was used, the film contained a lot of foreign matter and was somewhat inferior as a film for industrially continuous production.

[0135] In Comparative Example 4, no inner pipe was used to supply the raw materials, and the raw material ratio fluctuated greatly in the longitudinal direction due to segregation of the raw materials, so that the arithmetic mean height Sa and maximum projection height Sp of the obtained film roll varied greatly in the longitudinal direction. Although a good film having physical properties equivalent to those of Examples 1 to 4 in some parts of the film roll was obtained, the film roll was inferior as a film roll for industrial continuous production.

[0136] [Table 2A]

[0137] [Table 2B] [Industrial Applicability]

[0138] The biaxially oriented polyester film roll of the present invention has excellent transparency and mechanical properties, and is also excellent in terms of slipperiness and winding properties during the film production process. By using polyester resin recycled from the market and society, including PET bottles, it is possible to provide a biaxially oriented polyester film roll made of an environmentally friendly polyester film, which contains little foreign matter and has little variation in physical properties in the longitudinal direction even in a long film roll with a long wound length, and a production method thereof. This technology can be widely used in the field of packaging films, such as food packaging and gas barrier films, and is expected to make a significant contribution to the industrial sector, as there is a strong desire in recent years to reduce the environmental impact.

Claims

1. A biaxially oriented polyester film roll obtained by winding up a biaxially oriented polyester film made of a polyester resin composition containing a polyester resin and particles, the biaxially oriented polyester film roll being obtained by recycling polyethylene terephthalate containers, and satisfying all of the following requirements (1) to (5). (1) The maximum projection height Sp on at least one of the film surfaces is 3.0 μm or less. (2) The haze is 10% or less at a film thickness of 12 μm. (3) The dynamic friction coefficient between one side of the film and the opposite side is 0.26 or more and 0.45 or less, and the static friction coefficient is 0.25 or more and 0.46 or less. (4) When sampling is performed every 1000 m in the longitudinal direction of the film from the surface layer of the film roll to the core, the variation in both the arithmetic mean height Sa and the maximum projection height Sp is 40% or less. (The variation is expressed by the following formula [1], where the maximum value is Xmax, the minimum value is Xmin, and the average value is Xave. Variation (%) = 100 x (Xmax - Xmin) / Xave... [1] (5) The time required for air to escape between the front and back surfaces of the film is 14 seconds or less.

2. 2. The biaxially oriented polyester film roll according to claim 1, wherein the polyester resin recycled from the polyethylene terephthalate container according to claim 1 is a mechanically recycled polyester resin and / or a chemically recycled polyester resin.

3. The biaxially oriented polyester film roll according to claim 1 or 2, characterized in that the content of an isophthalic acid component relative to 100 mol% of all dicarboxylic acid components in the polyester resin composition constituting the biaxially oriented polyester film is 0.01 mol% or more and 2.0 mol% or less.

4. 4. The biaxially oriented polyester film roll according to claim 1, wherein the number of defects of 1 mm or more per 100 m2 of the film is less than 20.

5. 5. The biaxially oriented polyester film roll according to claim 1, wherein the content of inorganic particles in all layers of the biaxially oriented polyester film is 100 ppm or more and 1000 ppm or less.

6. The biaxially oriented polyester film roll according to any one of claims 1 to 5, characterized in that the polyester resin recycled from the polyethylene terephthalate container is a polyester resin obtained by mechanically recycling a PET bottle that has been subjected to at least one alkali wash.

7. 7. A method for producing a biaxially oriented polyester film roll according to any one of claims 1 to 6, comprising a polyester raw material resin melt extrusion step, a biaxial stretching step, and a step of winding up the biaxially stretched film into a roll, wherein in the polyester raw material resin melt extrusion step, raw material resin chips of the polyester resin recycled from the polyethylene terephthalate container are supplied from above to a hopper, and raw material resin chips of a polyester resin composition containing the particles are supplied through a pipe in the hopper having an outlet immediately above the extruder, to mix the two chips and melt extrude them.

Citation Information

Patent Citations

  • Steam iron

    JP1985036099A

  • Recycled polyester-containing polyester structure and method for manufacturing the same

    JP2011256328A

  • Heat-shrinkable polyester-based film roll

    WO2019065108A1

  • Polyester film roll

    WO2019187694A1

  • Biaxially oriented polyester film roll

    WO2020090673A1